Combinational therapeutic targeting of BRD4 and CDK7 synergistically induces anticancer effects in head and neck squamous cell carcinoma. (28th January 2020) - Zhang, Wei; Ge, Han; Jiang, Yue; Huang, Rong; Wu, Yaping; Wang, Dongmiao; Guo, Songsong; Li, Sheng; Wang, Yanling; Jiang, Hongbing; Cheng, Jie
Abstract: The bromodomain and extra-terminal domain protein BRD4 has been recognized as a key oncogenic driver and a druggable target against cancer. However, these BRD4 inhibitors as monotherapy were moderate in efficacy in preclinical models. Here we utilized a small-scale drug synergy screen that combined the BRD4 inhibitor (JQ1) with 8 epigenetic or transcriptional targeted chemicals and identified THZ1 (a CDK7 inhibitor) acting synergistically with JQ1 against head neck squamous cell carcinoma (HNSCC). Combinational JQ1 and THZ1 treatment impaired cell proliferation, induced apoptosis and senescence, which were largely recapitulated by dual BRD4 and CDK7 knockdown. Combinational treatment inhibited tumor growth and progression in 4NQO-induced HNSCC and xenograft animal models. RNA-sequencing analyses identified hundreds of differentially expressed genes modulated by JQ1 and THZ1, which were significantly enriched in categories including cell cycle and apoptosis. Mechanistically, combinational treatment reduced H3K27ac enrichment in the super-enhancer region of YAP1, which inactivated its transcription and in turn induced anti-proliferative and pro-apoptotic effects. Combined BRD4 and CDK7 upregulation associated with worst prognosis in HNSCC patients. Collectively, our findings reveal a novel therapeutic strategy of pharmacological inhibitions of BRD4 and CDK7 against HNSCC. Highlights: Drug combination screen identified THZ1 as acting synergistically with JQ1 in HNSCC cells. JQ1 and THZ1 synergistically impaired cell proliferation and induced cell apoptosis and senescence in vitro. Combinational JQ1 and THZ1 treatment inhibited tumor growth and progression in two preclinical HNSCC animal models. YAP1 was identified as the key mediator for the synergistic therapeutic effects conferred by JQ1 and THZ1 exposure.